2020
DOI: 10.5114/nan.2020.97398
|View full text |Cite
|
Sign up to set email alerts
|

Analytical study of adult attention deficit hyperactivity disorder symptoms and internet addiction among medical students

Abstract: Introduction: Adult attention deficit hyperactivity disorder (ADHD) has a prevalence of 4.4% worldwide. Adults with ADHD are more prone to risk taking behaviours, behavioural addictions and substance abuse. Studies have shown that adults with ADHD are more likely to develop internet addiction (IA). Aim of the study: To determine scoring of medical students on an adult ADHD scale and internet addiction scale and to compare it. To compare the scoring in context to demographic characteristics and substance use. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Current literature shows that ADHD symptoms are related with forms of technology addiction (e.g., Andreassen et al, 2016;Hussain & Griffiths, 2021;Hussain & Wegmann, 2021) as was shown in this study. Although it has been found that the inattention symptom is the most related symptom for many forms of TA (Panagiotidi & Overton, 2020;Wang et al, 2017), most of the explanations such as a reduced ability to react to punishment (Kandre et al, 2020) or seeking immediate rewards (Wang et al, 2017) are related to the features of impulsivity (Salehinejad et al, 2021). Therefore, the role of the symptom of inattention in forming TAs needs to be confirmed and further investigated experimentally.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Current literature shows that ADHD symptoms are related with forms of technology addiction (e.g., Andreassen et al, 2016;Hussain & Griffiths, 2021;Hussain & Wegmann, 2021) as was shown in this study. Although it has been found that the inattention symptom is the most related symptom for many forms of TA (Panagiotidi & Overton, 2020;Wang et al, 2017), most of the explanations such as a reduced ability to react to punishment (Kandre et al, 2020) or seeking immediate rewards (Wang et al, 2017) are related to the features of impulsivity (Salehinejad et al, 2021). Therefore, the role of the symptom of inattention in forming TAs needs to be confirmed and further investigated experimentally.…”
Section: Discussionmentioning
confidence: 98%
“…People with ADHD have inhibition and cognitive control problems (Panagiotidi & Overton, 2018;Wang et al, 2017), exhibit a reduced ability to react to punishment (Kandre et al, 2020) and tend to seek immediate rewards (Wang et al, 2017). Furthermore, they display sensation-seeking personality traits, a need for new, varied, and complicated experiences and sensations, as well as a readiness to take risks to fulfil this need (Panagiotidi & Overton, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 50 studies were included in the systematic review based on Young's criteria cut-off scores of 50 (Y-IAT ≥50; n=20 901, k=42) and 40 (Y-IAT ≥40; n=2816, k=8). [59][60][61][62][63][64][65][66] The included studies' characteristics are summarised in tables 1 and 2. The sample population covered young adults in the age group 17 to 35 who were pursuing their careers in the medical and engineering science stream (n=15 262, k=39) and allied courses such as basic Science and arts stream (n=8455, k=11).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Some confirmation with respect to the age trend involved in such issues comes from studies that have recently focused on the Internet addiction of workers and professionals ( 108 111 ). Other studies also point out the association between Internet addiction (in both adults and young adults) with depression ( 43 , 112 114 ), hyperactivity and attention deficit ( 115 119 ).…”
Section: Discussionmentioning
confidence: 99%